Different gene expression of skin tissues between mice with weight controlled by either calorie restriction or physical exercise - Lu, Jia; Xie, Linglin; Sylvester, Jessica; Wang, Jiasong; Bai, Jianfa; Baybutt, Richard; Wang, Weiqun (My University, 2008)
Cancer prevention by weight control via dietary calorie restriction (DCR) and/or exercise has been demonstrated in animal models. To understand the underlying mechanisms, we compared phorbol ester (TPA)-induced gene expression profiles in DCR- or exercise-treated mouse skin tissues. SENCAR mice were randomly assigned to one of the following groups: ad libitum-fed sedentary control, ad libitum-fed exercise (AE), exercise but pair-fed at the amount of the control (PE), and 20% DCR. After 10 weeks, both body weight and fat composition significantly decreased in the DCR and PE groups compared with the controls. Weight loss was not observed in the AE group due, at least in part, to increased food intake. Among 39,000 transcripts with 45,101 probe sets measured by Affymetrix microarray, we identified 411, 110, and 67 genes that showed > 1.5-fold and significant changes by DCR, AE, and PE, respectively. Gene ontology showed a profound impact on gene expression by DCR in 21 biologic process categories. Although PE and AE had a moderate impact on gene expression, the similarity of gene expression pattern altered by PE was relatively closer to DCR, whereas AE was closer to the control. The results of 22 cancer-related gene expression patterns, especially for certain oncogenes, further supported that PE appeared to be a better alternative than AE to DCR-like cancer prevention. The impact on gene expression pattern was associated with the effect on weight loss (i.e., DCR >> PE > AE). Overall, this study demonstrated for the first time that weight control via decreasing energy intake or increasing energy expenditure resulted in the different modes of gene expression. DCR showed profound inhibitory impact on the expression of genes relevant to cancer risks. Furthermore, exercise along with limited calorie intake appears to be a better method for reducing weight and cancer risk compared with exercise alone.
Keywords: Weight control; Gene expression; Calorie restriction; Exercise; Cancer prevention; Mice